Women's experiences of care and support following perinatal death in high burden countries: A metasynthesis. Issue 2 (March 2023) - Kuforiji, Omotewa; Mills, Tracey A.; Lovell, Karina
Abstract: Problem: The experiences of women in low and middle-income countries following perinatal death remains difficult and challenging, thereby increasing their susceptibility to negative psychological impact particularly with insufficient bereavement care and support. Background: Perinatal death invariably brings intense grief which significantly impacts women, and requires adequate bereavement care to limit negative outcomes in the short and long-term. Aim: To develop deeper understanding of women's experience of care and support following perinatal death in high burden settings. Methods: Six electronic databases were searched with relevant terms established using the SPIDER tool, supplemented by hand search of reference lists. Studies were independently screened for inclusion by all authors. Meta-ethnography (Noblit and Hare, 1988) was used to synthesise existing qualitative studies. Findings: Eight studies conducted in Sub-Saharan African and South Asian countries namely South Africa, Uganda, Ghana, Kenya, India and Malawi were included, and three main themes were identified; mothers' reaction to their baby's death, care and support after perinatal death, and coping strategies in the absence of care and support. Perinatal death was not appropriately acknowledged therefore care and support was inadequate and, in some cases, non-existent. Consequently, mothers resorted to adopting coping strategies as they were unable to express their grief. Discussion: There is insufficient care and support for women following perinatal death in high burden settings. Conclusions: Further research is required into the care and support being given by healthcare professionals and families in high burden settings, thereby ultimately aiding the development of guidance on perinatal bereavement care.